Comparison the adsorption of Pb with Ecofriendly Bio-Adsorbent From Rice Husk Ash and Boiler Fly Ash - Tarigan, Enda Rasilta; Sitinjak, Anna Angela; Silalahi, Meriahni; Purba, Switamy Angnitha; Sitanggang, Yenny; Purba, Darry (International Journal of Applied Sciences and Smart Technologies, 2024)
The amount of environmental pollution is in line with the increasing of industry. Industry can generate waste in the form of solid, liquid or gas. Utilization of waste as an adsorbent is a solution that can be done in dealing with waste such as metal waste contained in water. Therefore, this research aims to make a bio-adsorbent in the form of silica from rice husk ash and boiler fly ash and know the comparison of the Pb absorbed. The research method used is an experimental method by synthesizing the manufacture of silica. Then testing of Pb based on contact time was 30 minutes, 60 minutes, 90 minutes and 120 minutes. The results showed that the two silica-based bio-adsorbents could adsorb Pb. Bio-adsorbent from rice husk ash absorbed 56.51% of Pb in 30 minutes, 52.93% in 60 minutes, 48.65% in 90 minutes and 43.55% in 120 minutes. The bio-adsorbent from the fly ash boiler absorbed 50.15% of Pb in 30 minutes, 44.28% in 60 minutes, 38.48% in 90 minutes and 36.45% in 120 minutes. Bio-adsorbent from rice husk ash absorbs more Pb ions than from boiler fly ash. Because the silica in the rice husk ash forms a collection in the pores, whereas in the fly ash boiler there is silica that is spread out. This research can be a basis for further research in the form of dye bio-adsorbent products based on their short use time.